(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: CNS Infection are likely to arouse tremendous anxiety in both the physician and the patients. It is one of the most potentially serious infections occurring in children and important cause of mortality and morbidity in worldwide. Laboratory surveillance of pathogen is crucial in formulating the empirical treatment guidelines. To evaluate sociodemographic characteristics, clinical profile and pattern of pathogens of meningitis in children. Materials and methods: A descriptive study was carried out in paediatric Inpatient Department of Pediatric CMCH (Chittagong Medical College Hospital) Chattogram during the period of May 2013 to April 2014 where History, clinical examination and CSF sample were obtained from 40 patients of suspected meningitis. Diagnosis was based on the clinical presentation and CSF analysis. Results: In this study, out of 40 patient, 25 patients were diagnosed as bacterial meningitis and 15 patient were diagnosed as aseptic meningitis based on clinical features and CSF analysis. 20% Culture positive bacterial menigitis was found, S pneumonae was found the leading pathogen. Overall, mortality rate was 2.5 %. Conclusion: Bacterial meningitis is a medical emergency. Making an early diagnosis and prompt treatment are lifesaving. For Starting early empirical treatment of meningitis, knowledge about the local pathogen is necessary. JCMCTA 2022 ; 33 (1) :77-81